Representatives and directives as core communicative acts: Evidence from illocutionary patterns in Masameer County animation - Ridha, Muhammad Syahid; Nisa', Mauidlotun; Suparno, Darsita; Helmanita, Karlina; Anas, Muhammad (Al-Lisan: Jurnal Bahasa, 2025)
Background: Understanding speech acts in animation is important because misunderstandings can affect communication across cultures. The Masameer County animation, popular among Arabic speakers, contains dialogues with cultural meanings that need deeper study.Aims: This research aims to analyse the categories and functions of illocutionary speech acts in Masameer County's animated dialogue.Methods: This research uses qualitative content analysis with some quantitative support, focusing on pragmatics. The Arabic dialogues and their Indonesian subtitles are transcribed and analysed to identify illocutionary speech acts. John Searle's theory is applied to examine the categories and functions of these speech acts in the Masameer County episodes "Ice Cream" and "Washingtonia".Results: Out of 443 utterances, 269 were identified as illocutionary speech acts. Representatives predominated with 153 data, such as claiming and describing, followed by directives with 94 data, including commanding and requesting. Commissive (14 data) and expressive (8 data) appeared less frequently, with promising and regretting being the most common within these categories. Declarative speech acts were not found, indicating the narrative's focus on personal interaction.Implications: The dominance of representatives and directive speech acts suggests that the communication style in Masameer County primarily revolves around the core functions of human interaction. This finding affirms the universal relevance of Searle's theory of illocutionary speech acts in analysing animated media.